Cloth Face Masks Containing Silver: Evaluating the Status - Blevens, Melissa S; Pastrana, Homero F; Mazzotta, Hannah C; Tsai, Candace Su-Jung (ACS Chemical Health & Safety., 2021)
Amid the coronavirus disease 2019 pandemic, demand for cloth face masks containing nanosilver has increased. Common product claims such as "antiviral" and "antimicrobial" can be attractive to buyers seeking to protect themselves from this respiratory disease, but it is important to note that filtration capabilities are the main factor to prevent virus transmission and that antimicrobial ability is a secondary protection factor. Silver has long been known to be antibacterial, and growing research supports additional antiviral properties. In this study, 40 masks claiming to contain silver were evaluated for substantiated antiviral and antimicrobial claims using methods available to the public. Criteria for determining the validity of substantiated claims included the use of patented technology, international certification for antimicrobial and/or antiviral textile by ISO or ASTM, EPA pesticide registration, and peer-reviewed literature. Our analysis showed that, of the 40 masks, 21 had substantiated claims. Using scanning electron microscopy (SEM), two of the substantiated face masks (A and B) were examined for silver identification for further confirmation. Mask A uses silver and copper ions attached to zeolite particles; the zeolite particles discovered through SEM were approximately 90-200 nm in diameter. In mask B, particles of silver and titanium at the 250 nm size were found. In conclusion, these certifications or patents are not enough to determine credibility, and stricter regulations by federal agencies on product testing for manufacturers that make claims are necessary to ensure the efficacy of the product advertised, as well as a cloth face mask inhalation standard.